2018
DOI: 10.1038/s41467-018-05098-4
|View full text |Cite
|
Sign up to set email alerts
|

Glycan recognition in globally dominant human rotaviruses

Abstract: Rotaviruses (RVs) cause life-threatening diarrhea in infants and children worldwide. Recent biochemical and epidemiological studies underscore the importance of histo-blood group antigens (HBGA) as both cell attachment and susceptibility factors for the globally dominant P[4], P[6], and P[8] genotypes of human RVs. How these genotypes interact with HBGA is not known. Here, our crystal structures of P[4] and a neonate-specific P[6] VP8*s alone and in complex with H-type I HBGA reveal a unique glycan binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 64 publications
7
87
1
Order By: Relevance
“…Structural-based sequence alignment of P [19], P [6], P [4] and P [8] showed that they have high levels of amino acid conservation. From the recent crystallization studies, it was found that P [19], P [6], and P [4] employed the βα binding domain to accommodate H type 1 ligand LNFP I [35,36], which is in agreement with our NMR-driven HADDOCK results. Previous homology modeling results suggested that the addition of Lewis fucose via α1,4-linkage to the O4 atom of the GlcNAc residue could cause a binding clash if P [8] used the same binding interface as P[4] [36].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Structural-based sequence alignment of P [19], P [6], P [4] and P [8] showed that they have high levels of amino acid conservation. From the recent crystallization studies, it was found that P [19], P [6], and P [4] employed the βα binding domain to accommodate H type 1 ligand LNFP I [35,36], which is in agreement with our NMR-driven HADDOCK results. Previous homology modeling results suggested that the addition of Lewis fucose via α1,4-linkage to the O4 atom of the GlcNAc residue could cause a binding clash if P [8] used the same binding interface as P[4] [36].…”
Section: Discussionsupporting
confidence: 88%
“…From the recent crystallization studies, it was found that P [19], P [6], and P [4] employed the βα binding domain to accommodate H type 1 ligand LNFP I [35,36], which is in agreement with our NMR-driven HADDOCK results. Previous homology modeling results suggested that the addition of Lewis fucose via α1,4-linkage to the O4 atom of the GlcNAc residue could cause a binding clash if P [8] used the same binding interface as P[4] [36]. Our structural studies presented here resolve this perceived conflict, showing that P [8] accommodates the Le b -containing ligands by shifting to a new binding site, namely the  binding domain.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…P [19] genotype (a genotype that infects pigs and humans), belongs to the genogroup II and binds to the H antigen and to the mucin core 2 glycan 21 . In the same manner, P [4], P [6] and P [8] that also belong to the genogroup II, are able to recognize H type related antigens and the type I precursor 5,22 . Finally the P [11] genotype interacts with the H type II precursor molecule 18 .…”
Section: Discussionmentioning
confidence: 94%